2010
DOI: 10.1002/bem.20632
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic effects on forearm disuse osteopenia: A randomized, double-blind, sham-controlled study

Abstract: A randomized, double-blind, sham-controlled, feasibility and dosing study was undertaken to determine if a common pulsing electromagnetic field (PEMF) treatment could moderate the substantial osteopenia that occurs after forearm disuse. Ninety-nine subjects were randomized into four groups after a distal radius fracture, or carpal surgery requiring immobilization in a cast. Active or identical sham PEMF transducers were worn on the distal forearm for 1, 2, or 4 h/day for 8 weeks starting after cast removal ("b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…In contrast to the above‐mentioned studies, no significant increase in BMD after 3 months could be found in a single‐blind and randomized pilot study [Giordano et al, ], which adopted the following parameters: 100 Hz and 10 ± 2 G PEMF exposure. Similarly, another randomized and sham‐controlled study [Spadaro et al, ] found that the parameters of 8 weeks, 15 Hz, and 2 mT PEMFs did not result in long‐term positive changes in BMD in subjects with forearm disuse osteopenia, after adjusting for age, gender, and baseline BMD.…”
Section: Clinical Advances In Research Of Pemfs On Pmopmentioning
confidence: 90%
See 1 more Smart Citation
“…In contrast to the above‐mentioned studies, no significant increase in BMD after 3 months could be found in a single‐blind and randomized pilot study [Giordano et al, ], which adopted the following parameters: 100 Hz and 10 ± 2 G PEMF exposure. Similarly, another randomized and sham‐controlled study [Spadaro et al, ] found that the parameters of 8 weeks, 15 Hz, and 2 mT PEMFs did not result in long‐term positive changes in BMD in subjects with forearm disuse osteopenia, after adjusting for age, gender, and baseline BMD.…”
Section: Clinical Advances In Research Of Pemfs On Pmopmentioning
confidence: 90%
“…Though negative BMD change was reported in a trial [Giordano et al, ], the authors found that PEMF exposure with parameters of 100 Hz and 2.85 mT (60 min/day, 3 times a week for 3 months) could increase serum osteocalcin (OC) and PINP levels, which were biomarkers associated with bone formation. Similarly, PEMFs with parameters of 8 weeks, 15 Hz, and 2 mT maintained the expected normal level of serum bone‐specific alkaline phosphatase (BSAP) and decreased CTX level, which were independent of BMD change, but were still beyond normal levels in patients with forearm disuse osteopenia [Spadaro et al, ].…”
Section: Clinical Advances In Research Of Pemfs On Pmopmentioning
confidence: 99%
“…Since no previous study was ever conducted regarding the effect of PEMFs on PMO, especially with these very parameters, it seems theoretically impractical to calculate the sample size. Instead, we estimated it to be 20 per group, similar to that of the study exploring the treatment effect of PEMFs on forearm disuse osteopenia [Spadaro et al, 2011]. To test the rationality of this estimation, we calculated the statistical power for the primary endpoint, the mean percentage change in bone mineral density of the lumbar spine (BMDL), from baseline at the last visit.…”
Section: Methodsmentioning
confidence: 99%
“…Since then, much evidence has positively supported the treatment effect of PEMFs for osteoporosis, although with an effective window [Rubin et al, 1989; Tabrah et al, 1990; Eyres et al, 1996; Garland et al, 1999; Giordano et al, 2001]. In addition, various biochemical mechanisms have been associated with its effectiveness [Shankar et al, 1998; Chang and Chang, 2003; Sun et al, 2009; Chen et al, 2010; Shen and Zhao, 2010] and there seems to be no detrimental side effects [Blaszczak et al, 2009] or sufficient amplitude to elicit neuromuscular responses [Radon et al, 2001; Spadaro et al, 2011]. But, negative results were also reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation